ANALISIS KUALITAS LAYANAN PERUSAHAAN DAERAH AIR MINUM PADA PELAYANAN AIR BERSIH DI KECAMATAN TIRAWUTA KABUPATEN KOLAKA TIMUR - Fetni; Sudirman Baso; Anis Ribcalia Septiana (Halu Oleo University, 2023)
The research aims to analyze the quality of PDAM Tirta Simbune services in East Kolaka Regency, with a focus on clean water services in Tirawuta District. East Kolaka Regency has abundant water resource potential, but there are still various challenges in providing quality and adequate drinking water to the community. This research uses secondary data analysis methods and customer surveys to identify existing problems and increase understanding of customer needs and expectations for PDAM services. Data was collected from PDAM, the local government, and through a survey involving several PDAM customers in Tirawuta District. The research results illustrate that the service quality of PDAM Tirta Simbune is quite good when seen from direct evidence, reliability, responsiveness, assurance and empathy, but there is still a need for improvements in facilities and infrastructure. Meanwhile, factors that influence service quality are external influences and also internal influences. Internal influences can relatively be controlled by the company, for example, facilities and infrastructure, discipline, employee responsibility, employee ability, politeness, speed of response, ease of service procedures, suitability of procedures, clarity of service, and thoroughness of transactions, while external influences such as building relationships with customers, flow Dry season, rainy season flow and professionalism in resolving customer complaints.